KEMAMPUAN MENCERITAKAN TOKOH IDOLA DENGAN MEDIA GAMBAR - Gafar, Abdoel (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
This research purposes is to describing of ability to tell the idol figures with image media for junior high school students No. 10 class VII.1 in Jambi city school year 2013/2014. The methods that used in this research is qualitative descriptive method. The result research from 34 students, most of 7 students is getting value with excellent ranked, 23 students is getting with good ranked and 4 students can gets the value with standard ranked that getting on overall values 2772 with averages values 81,52 is good ranks. The conclution that using image media to tell idol figures for the junior high school students No.10 class VII.1 Jambi city school year 2013/2014 with good predicates. Keywords: speaking, idol figures, image media